Inpatient Satisfaction Level Regarding the Quality of Services at Tamberu Barat - Sari, Agoesta Pralita; Sari, Isnaini Novita; Jamila, Fajarirayul; Watiningrum , Rahayu Yuliana (Jurnal Sains dan Teknologi Kesehatan, 2025)
Introduction: The quality of healthcare services is reflected in the level of patient satisfaction. Patient satisfaction is the feeling experienced by patients as a result of the performance of healthcare services, which is assessed by comparing the services received with their expectations. If the healthcare services meet or exceed patients’ expectations, they will feel satisfied. This study aims to explore and understand the main reasons why most of the community prefers to use other community health centers (puskesmas) instead of Tamberu Barat Community Health Center as their primary healthcare facility. Methods: This study used a descriptive research strategy. The population consisted of 100 patients. The sample was determined using the Slovin formula. A non-probability sampling method, specifically purposive sampling, was used in this study. Results: It was found that for the reliability dimension, 73 respondents were satisfied, while 7 were not. For the assurance dimension, 73 respondents were satisfied and a small number, 7 respondents, were not. For the tangibility dimension, 71 respondents were satisfied and 9 were not. For the empathy dimension, 73 respondents were satisfied and 7 were not. For the responsiveness dimension, 73 respondents were satisfied and 7 were not. Conclusion:In terms of inpatient satisfaction: 73 respondents were satisfied with the reliability dimension; 70 respondents were satisfied with the assurance dimension; 73 respondents were satisfied with the tangibles dimension; 73 respondents were satisfied with the empathy dimension; and 73 respondents were highly satisfied with the responsiveness dimension. Recommendation: All healthcare staff at the Puskesmas are advised to pay more attention to the completeness of medical equipment and to provide services in accordance with the predetermined schedule Keyword: Quality of service, Inpatient care, Satisfaction level